Strategi Pelatihan SDM: Mendorong Kompetensi dan Kualitas Layanan Hotel Puncak Pass - Euis Balillah; Dendi Supiyandi; Sri Sumarni; Herlina (PT. Alahyan Publisher Sukabumi, 2026)
This study aims to empirically examine and evaluate the effect of training programs on employee competency levels and their impact on the quality of hospitality services at Puncak Pass Hotel Cianjur. Amid the intense competition in the hospitality industry within tourist destination areas, the quality of interactions between employees and guests has become a key determinant of hotel competitiveness. This research employed a quantitative approach with an explanatory research design. The sampling technique used was saturated sampling, involving all operational employees as respondents, totaling 30 individuals. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).The results of the data analysis reveal that the implementation of training programs has a positive and significant effect on improving employee competencies. However, training programs do not have a significant direct effect on enhancing hotel service quality. Furthermore, employee competency was also found to have no significant effect on service quality, indicating that competency is unable to mediate the relationship between training and hotel service quality. These findings suggest that hotel management needs to redesign the evaluation mechanisms and training materials so that they are not merely administrative in nature, but are genuinely aligned with practical operational needs in the field